Coupling between a calix[6]arene-based chromatography column and ICP-MS for on-line actinide analysis. Issue 7 (11th May 2016) - Baghdadi, S.; Cote, G.; Beyaert, C.; Mane, B.; Peroux, A.; Masclet, L.; Rebiere, F.; Agarande, M.; Bouvier-Capely, C.
Abstract : Analysis of actinides by coupling a calix[6]arene column to a Q-ICP-MS for emergency situations. Abstract : A method based on the coupling of a calixarene column used for the preconcentration of actinides to a quadrupole ICP-MS was developed for the separation of actinides and their on-line detection. First, a flow injection system was developed for aqueous U, Pu and Am on-line ICP-MS analysis. Then, chromatography parameters such as the column diameter and flow rates were optimised using the theoretical plate model. The detection limits achieved are 0.6 ng (7 μBq) for 238 U, 16 pg (37 mBq) for 239 Pu and 0.21 pg (27 mBq) for 241 Am. The signal improvement achieved by this coupling method was discussed and compared to "dilute and shoot" analysis. Finally, this method was validated on certified reference materials of 238 U, 239 Pu and 241 Am, at concentration levels close to the detection limits.